The Relationship Between Pregnant Women's Attitudes Towards Taking Iron Tablets And The Incidence Of Anemia - Lina Herlina; Rosita Rosita (Sean Institute, 2025)
Anaemia among pregnant women poses a significant risk, serving as an indirect contributor to maternal mortality and negatively impacting pregnancy outcomes. This circumstance, characterized by a deficiency of red blood cells, hampers the delivery of oxygen to bodily tissues, a situation worsened by the heightened demands of pregnancy. Iron deficiency anaemia can lead to various complications, including impaired fetal growth, premature delivery, low birth weight, increased vulnerability to infections, and even fetal demise. The objective of this research is to explore the connectionamong pregnant women's attitudes towards the consumption of iron (Fe) tablets and the prevalence of anaemia. Utilizing a cross-sectional research design and purposive sampling technique, the findings revealed that 36.7% of participants held a negative attitude towards Fe tablets. Furthermore, a moderate correlation was identified among the attitudes of pregnant women regarding Fe tablet consumption and the incidence of anaemia, as indicated by a contingency C value of 0.370. This suggests that the attitudes of pregnant women significantly influence their adherence to Fe tablet inhave. Therefore, maternal and child health programs should have attitudinal factors into account to enhance compliance by Fe tablet consumption, ultimately reducing the risk of anaemia and associated pregnancy complications. Implementing effective behavior change interventions can significantly improve both maternal and infant health outcomes.